Volontarism and informal diplomacy on emigration and work in the early 20th century: The career of Gugliemo E. di Palma Castiglione (Il Risorgimento. Rivista di storia moderna e contemporanea, 2025)
By following the career of an official, the article contributes to the discussion on the evolution of policies to protect Italian labour abroad between the liberal age and fascism. In 1902, Di Palma Castiglione joined the ‘informal diplomacy’ that the Foreign Ministry used to assist workers abroad during the ‘great migration’. In New York, he directed the Labour Office for Italians; he was sent to various locations in Europe and America to study work opportunities, according to the prevailing view among Italian authorities, who hoped to be able to direct migrants into large homogeneous groups, to keep the communities in close contact with the mother country. As an emigration expert he participated in the 1919 Peace Conference and was among the promoters of the International Labour Organisation, where he remained as an official until the 1930s.
Keywords: International Labour Organization – ILO, Italian immigration in the USA, Italian Commissariat General of Emigration – CGE, Italian labour office - New York